-34-2a=-3(5a-6)

Simple and best practice solution for -34-2a=-3(5a-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -34-2a=-3(5a-6) equation:



-34-2a=-3(5a-6)
We move all terms to the left:
-34-2a-(-3(5a-6))=0
We calculate terms in parentheses: -(-3(5a-6)), so:
-3(5a-6)
We multiply parentheses
-15a+18
Back to the equation:
-(-15a+18)
We get rid of parentheses
-2a+15a-18-34=0
We add all the numbers together, and all the variables
13a-52=0
We move all terms containing a to the left, all other terms to the right
13a=52
a=52/13
a=4

See similar equations:

| 5y+7-y=7+3y+8 | | 9x=4x+2 | | 50=5*h | | x+1/10=1/2 | | 6^x=45.6 | | 5(-1)-7y=13 | | X-14=-3x-2 | | 98/140=x/150 | | -12x^2+20x+8=0 | | x+2/9=5/9 | | 5=b+5/2 | | 12(0.11)+6(0.78)=18x | | 1/x=3.9 | | -21x+18=7x-22= | | 5(0)-7y=13 | | 7=5(v-4)-8v | | 8(8x)=96 | | 5=b+52 | | 5d-11=15+2d | | -8(3+r)=-96 | | 6y+2=6y-y | | x-8=-7-4x-1+7x | | 2x+9x+37=180 | | 40(3x)(2x)=180 | | 5(1)-7y=-13 | | F(-29)=-1/2x+3 | | 3x+14=58 | | 6d-12=16+2d | | (3y+3)+(3y+3)+(4y-1)+(4y-1)=158 | | 1/16=64^9x+5 | | -1+3y=-4 | | 36=3/4h |

Equations solver categories